The Ritschlian School the Essence of Christianity and Karl Barth - Deegan, D. L. (Scottish journal of theology, 1963)
William Hamilton has recently called our attention to the significance of the idea of the ‘essence of Christianity’ associated with the late nineteenth and early twentieth centuries. ‘… It is not at all clear’, writes Hamilton, ‘that the phrase itself does not still have some real usefulness. It is interesting that in Dietrich Bonhoeffer's final papers we have a projected outline for a little book that was to have been called The Essence of Christianity.’ Our aim in this essay is a reassessment of the significance of Ritschl, Harnack and Troeltsch as these sought to illumine from their own theological perspectives the essence of Christianity. We place Harnack and Troeltsch in the ‘Ritschlian School’ in the sense that both acknowledged Ritschl as their teacher and in spite of divergencies from him in their respective theologies nevertheless continued to note their indebtedness to him. We shall show that the effort to define the essence of Christianity is intimately associated in the work of each of these theologians with the search for right theological method.